The Influence of Discipline on Service Quality among Aryaduta Manado Hotel Bar Employees - Sadjab, Wahyu Pratama; Tenda, Mirjam P.; Lumare, Mercy A.; Sinolungan, Linda (Indo Consultan Energi, 2024)
Hotels are a type of accommodation that is vital to tourism development. The quality of service in hotel entities is an essential point that management needs attention to. This research examines the influence of discipline on service quality among employees of the Aryaduta Manado Hotel. This research uses a qualitative method with a descriptive approach. A descriptive approach is used to explain the research theme. Data was obtained through interviews and observations of the Bar Hotel Aryaduta Manado employees. The research results show that discipline influences the quality of employee service. The hotel industry must pay primary attention to work discipline, contributing to employee performance.